Causal effects of gut microbiota on erectile dysfunction: a two-sample Mendelian randomization study - Zhang, Yuyang; Chen, Yuxi; Mei, Yangyang; Xu, Renfang; Zhang, Hong; Feng, Xingliang (Frontiers in Microbiology, 2023)
Background: Several observational studies have reported the correlation between gut microbiota and risk of erectile dysfunction (ED). However, the causal association between them remained unestablished owing to intrinsic limitations confounding factors and reverse causality. So, the twosample mendelian randomization (MR) study was performed to determine the causal effect of gut microbiota on the risk of ED.The MR analysis utilized the publicly available genome-wide association study (GWAS) summary level data to explore the causal associations between gut microbiota and ED. The gut microbiota data were extracted from the MiBioGen study (N=18340), and the ED data were extracted from the IEU Open GWAS (ED cases: 6175 ED cases, and 217630 controls). The single nucleotide polymorphisms (SNPs) were served as instrumental variables (IVs) by two threshold of P values, the first P value setting as <1e-05 (locus-wide significance level) and the second P value setting as <5e-08 (genome-wide significance level). The inverse variance weighted was used for the primary approach for MR analysis, supplemented with the other methods. In addition, sensitivity analyses were performed to evaluate the robustness of the MR results, including Cochran's Q test for heterogeneity, MR-Egger intercept test for horizontal pleiotropy, Mendelian randomization pleiotropy residual sum and outlier (MR-PRESSO) global test for outlier, and forest test and leave-one-out test for strong influence SNPs.Results: Our results presented that the increased abundance of Lachnospiraceae at family level (OR:1.265, 95%CI: 1.054-1.519),